Effect of Processing Speed on Microstructure and Colour Properties of the Iron Ore-Derived Red Colour Pigment. (April 2020) - Woon, H. S.; Ewe, L.S.; Lim, K.P; Ismail, I.
Abstract: This study proposes a novel technique to convert local iron ores into industrial grade red colour pigments. The methods employed in this work include high-energy milling, ball milling, rod milling and high-energy blending. It was observed in the TEM results that high-energy milling using ø 3 mm balls running at 550 rpm produced the finest particles with a value of 73.13 nm and a specific surface area of 178.62 m 2 g −1, while ball milling and high-energy blending methods were similarly effective in producing nanoparticles with size of78.54 nm and 88.65 nm, respectively. The sample of high-energy milling at 550 rpm displayed noticeable alterations in colour values, but the lightness of high-energy blending samples was low in comparison to other methods. CIE L*a*b* colour values were analysed for all the samples and the results indicated that the value of a* for all the samples was greater than 18.0. This indicated that the samples are suitable for use as raw materials in red colour pigment production. Generally, the processing speeds utilized by the above mentioned methods resulted in significant changes in colour properties and its microstructure.